Developmental consultation in implementing career education programs - Young, Richard A.; Borgen, William A. (Canadian Journal of Counselling and Psychotherapy, 2012)
A model is proposed for the implementation of career education programs in schools. Career education is defined as having goals coincident with many of the objectives of education itself and is placed firmly within the context of psychological education. The process suggested for implementation of these programs is developmental consultation which L described as involving the counsellor in: (a) increasing staff awareness of the need for career education through recognition of commonality of goals between academic and career education, (b) focusing onpriorities for implementation of specific programs, (c) assisting in their operation, and (d) facilitating assessment of the effectiveness of career education programs implemented.